PENGARUH METODE PERCOBAAN TERHADAP LITERASI SAINS DAN HASIL BELAJAR KOGNITIF SISWA KELAS V SEKOLAH DASAR KECAMATAN CAKRANEGARA - Inang Irma Rezkillah; Zuhdan Kun Prasetyo (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
According to the results of PISA 2018 and researcher’s observations, scientific literacy skills and students' cognitive learning outcomes are still lacking. This study aims to determine the effects of science experiments on scientific literacy and student cognitive learning outcomes. This research design used a non-equivalent control group with a quasiexperimental type. The research sample was consisted of 3 fifth grade elementary schools located at Cakranegara region. The data were collected through tests and questionnaires filled out by students. Data were analyzed using independent sample t-test and MANOVA. The analysis showed the following results: first, the scientific literacy ability of students who took part in learning using the experimental method has significant more influential than students who took part in learning using the lecture method (tcount = 8.926; p <0.05). Furthermore, both cognitive learning outcomes of students who took part in learning using the experimental method were significantly more influential than students who took part in learning using the lecture method (tcount = 4.435; p <0.05). Third, the scientific literacy ability and cognitive learning outcomes of students who participated in learning using the experimental method were significantly more influential than students who participated in the lecture learning method (F = 42,375; p < 0.05). From these results, it could be concluded that the experimental method can be applied by teachers as one of the learning methods that has a positive influence on the progress of scientific literacy skills and students' cognitive learning outcomes in science learning